Estimation of technogenic load on the surface water of the North-Western Black Sea Coast region - Chugai, Angelina; Dzhura, Oksana (Lviv Politechnic Publishing House, 2019)
The paper considers the main sources of anthropogenic pollution of the surface waters of the North-Western Black Sea Coast regions. The level of anthropogenic loading on the surface water by the volumes of sewage and pollutant discharges into the water objects is estimated.
Keywords: surface water; discharge; module of technogenic load